Measurement of Shear Strain in Map Liquefaction Area for Earthquake Mitigation in Bengkulu City - Muhammad Farid; Arif Ismul Hadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Bengkulu city is well-known as a high-risk area for an earthquake. One of the effects of the earthquake is liquefaction, the phenomenon in which the strength and stiffness of the soil are reduced by shock. The researchers measured the quantity of liquefaction by knowing the value of Vs30 values that can be obtained from the United States Geological Survey (USGS). In this study, however, we measured liquefaction based on the shear strain value (γ). Here, the shear strain values could be determined by measuring the seismic vulnerability index and the peak ground acceleration. The vulnerability index was obtained by measuring the resonance of the frequency and the amplification factor using a short period seismometer with 3 components (2 horizontal components and 1 vertical component), whereas the peak ground accelerationα was obtained from the earthquake data that happened in Bengkulu City in 2000. The result showed that Vs30 and shear strain negatively correlated.